MOTIVASI: URGENSITASNYA DALAM PEMBELAJARAN YANG EFEKTIF - Fahimah, Siti (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2016)
In the process of education or learning, we often categorize children or adult into successful or unsuccessful. These terms of categorization are based on external monitoring. But the success of pupils depends largely on their motivation. There are pupils showing the laziness in learning because they lack motivation, internally or externally. They need positive motivation. There is intrinsic motivation, i.e. the motivation which emerges from inside the self or the motivation which is closely connected with the purpose. And there is extrinsic motivation, i.e. the motivation which comes from outside the self or the motivation which has no connection with the purpose. The motivation is intimately related to psychological condition. There are many theories of motivation, but they all go back to the individual state of a person. There are also several ways to raise motivation: 1) Creating competition, 2) Defining clear and recognized purpose, 3) Accomodating the interests of pupils. The purposes of motivation are: 1) to urge people to reach their goals, 2) to point them in the direction of their goals, and 3) to select carefully the appropriate action to reach the goals. The clear motivation can help teachers to carry out the more effective process of learning with the better results.Â Keywords: motivation, motive, psychology, learning effectiveness.